Cardiovascular Safety of Plant Sterol and Stanol Consumption. (27th November 2019) - Silbernagel, Guenther; Baumgartner, Iris; März, Winfried
Abstract: Plant sterols and stanols as components of functional foods are widely used for cholesterol lowering. The regular intake of these functional foods is associated with a decrease in low density lipoprotein cholesterol of about 10 % and an increase in plasma plant sterol or stanol concentrations by about a factor of 2. There is no doubt that a decrease in low density lipoprotein cholesterol is beneficial to cardiovascular health. However, due to the concomitant increase in circulating plant sterols safety issues associated with the intake of plant sterol containing functional foods have been raised. Herein, we will review and evaluate those arguments raised against the use of plant sterols and stanols.